Testing for camouflage using virtual prey and human 'predators' - Todd, Peter A (Journal of biological education, 2009)
Camouflage is a prevalent feature of the natural world and as such has a ready appeal to students; however, it is a difficult subject to study using real predators and prey. This paper focuses how one fundamental type of camouflage, disruptive colouration (bold markings that break up the outline of the organism), can be tested using paper printouts of prey and background, with humans as predators. Crypsis, i.e. when an organism resembles its background, will also be discussed. The shore crab (Carcinus maenas L.) was used as a model organism as it often possesses white markings that potentially camouflage it via disruptive colouration and crypsis. To test whether crab morphs with high contrast spots at the carapace edge were more difficult to find on a complex background than other pattern and contrast combinations, the time it takes human volunteers to find stylised images of crabs on paper printouts is taken as a measure of their camouflage. This approach has successfully been used for individual, group and class work in undergraduate-level ecology and behaviour modules to introduce organism-environment and predator-prey concepts.